Growth and Development of Sourgrass Plants from Vegetative Parts of Clumps - GAZOLA,T. (2019)
ABSTRACT: Sourgrass (Digitaria insularis) is a perennial plant with high infestation potential, has fast and aggressive development, and reproduces by seeds and rhizomes. D. insularis infestations have increased in agricultural areas without cover crops established between the main crop seasons. The control of this species has become one of the most expensive in these areas in Brazil. The present work evaluated the growth and development of D. insularis plants from different vegetative parts of clumps. Two greenhouse experiments were conducted in a completely randomized design, with four replications. A 5 × 4 factorial arrangement was used, with factor A corresponding to the different propagation methods, and factor B corresponding to the biotypes used (experiment 1) and the different planting depths evaluated (experiment 2). The parameters evaluated in all experiments were: rate of tiller emergence, number of tillers, flowering time, number of inflorescences, and shoot dry weight. Fragments of different parts of the sourgrass clumps, planted at up to 7 cm depth, can generate a new plant. The management of perennial plants of sourgrass by using plows, harrows, or cultivators favors the dispersal of this species.